Analisis Faktor Penghambat Remaja dalam Melanjutkan Pendidikan ke Perguruan Tinggi - Badriatus Shalihah; Firda Ayu Wahyuni (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2023)
This article aims to investigate the reasons behind the decision of youth graduates from SMK/SMA/MA/equivalent in Sentol Laok Village, Pragaan District, Sumenep Regency, to discontinue their education and the role of the village in addressing this phenomenon. The study employs a descriptive qualitative research design, utilizing interviews and documentation as data collection methods. The findings reveal several factors contributing to the discontinuation of education among youth in Sentol Laok Village, including (1) lack of motivation and interest, (2) the desire for immediate independence and employment, (3) economic constraints within families, and (4) the influence of the surrounding environment. The village plays a significant role in addressing this issue by providing motivation and fostering a sense of aspiration among adolescents to pursue higher education.